THE DEVELOPMENT OF ONLINE TUTORIAL MOODLE TO INCREASE THE EFFECTIVENESS OF LECTURES DURING PANDEMIC COVID-19 - Sukardi; Ratna Pancawati; Galfri Siswandi (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
Efforts can be done to increase the effectiveness of conventional learning process by making additional interaction extension outside classroom. In this regard, information technology can be utilized. The use of information technology which has same function as the conventional inside classroom learning provided in online learning. This research aims at testing the validity and practicality of Moodle online tutorial. The research uses development design (R&D). The research results show that online tutorial Moodle is valid (95,37%) and practical (80,36%) hence can be used in the online class widely.